Answers

2014-06-21T10:37:38+08:00
Note the standard form of quadratic equation Ax² + Bx + C = 0.

First divide the whole equation by 2:  to make A=1.

            2x² + 6x + 4 = 0 ....................divide by 2
              x² + 3x +2 = 0
              x² + 3x = -2     ....................transposing 2 to the other side of the equation.

Get (B/2A)² :
                    = (3/2)²
                    = 9/4  .........................ADD this to both sides of the equation.

We will have:

             x² + 3x + 9/4 = -2 + 9/4
                  (x + 3/2)² = 1/4.....................take the SQUARE ROOT of both sides.
                  x + 3/2 = +/- 1/2

                        x₁ = 1/2 - 3/2                          x₂ = -1/2 - 3/2
                        x₁ = -1                                   x₂ = -2 
0